Sensory Evaluation Scores of Iron-Enriched Food Supplement by using Avocado (Persea americana L.), Dates (Phoenix dactylifera L.) and Beetroots powder (Beta Vulgaris L.) - Anupam Maity; Bidisha Maiti Mondal; 3Chandrasekhar SM; Ranajit Kumar Khalua (The Bioscan, 2024)
This study investigates the sensory properties of an iron-enriched food supplement formulated with varying proportions of avocado and dates, enriched with different concentrations of beetroot powder. The purpose of this research is to analyze the effect of avocado-date ratios and beetroot powder concentrations on the sensory characteristics, including color, texture, flavor, and overall acceptability. Sensory evaluation was conducted using a structured 9-point hedonic scale by a panel of trained evaluators. Findings indicate that both avocado-date ratios and beetroot concentrations significantly influence sensory acceptability, with the 70:30 avocado-date ratio at 2% beetroot powder (T8) achieving the highest overall score.